Fokus Kajian Empirisme Dalam Ilmu Administrasi Publik - Ananta Eka Prastiwi; Cindy Silalahi; Fidyah Setia Argarini; Refina Mega; Salum Rifa Amalia (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Administration is an activity and business related to the implementation of policies to achieve a goal or process of organizing work that has been determined. Public Administration is a science that studies state management systems and those related to public interests and policies that are required to be responsible in public services. Then administration can be carried out through human experience which will later produce a knowledge called empirical science. Empirical science itself is an experience that is obtained from sensory experience. In this journal, it will specifically discuss the study of Empiricism in Public Administration. The science of public administration and empiricism cannot be separated because public administration requires empirical data to obtain a decision in public policy. Public administration also requires the science of empiricism to study how to create good public services for a country, so that people get comfort and safety in carrying out social interactions in the public.